Penguatan Hukum Merek dalam Perjanjian Lisensi Guna Peningkatan Taraf Ekonomi Masyarakat di Indonesia - Elza Syarief; Rina Shahriyani Shahrullah; Febri Jaya; Jendris Sihombing (Kosmik Hukum, 2021)
The issue of licensing agreements to improve the standard of living of people in Indonesia is very interesting to be studied in depth via intellectual discussions. Various problems should be taken as lessons for Indonesian people, for example: registration of the Toraja coffee trademark by the American businessmen, sambal uleg from Central Java and Gayo coffee by the Dutch and the song Sayang Sayange from Maluku and the legend of Garlic and Onion by Malaysia. The purpose of writing this article is to provide an explanation of the necessity to strengthen understanding of trademark law in the license agreement as an effort to improve the economic level of the Indonesian people. The problems focus on the government actions against the violations of Intellectual Property Rights (IPR) and as well as the roles of the government and society to improve the economic level of society through strengthening trademark law in license agreements. The research was conducted by using a normative legal research. The result of the research described in this article is that the economic level of the community can be increased by conducting a franchise business, providing opportunities for the franchisor to exploit economic rights in order to multiply and get the maximum profit at a low cost because it is borne by the franchisee.Keywords: Trademark, License Agreement, Economic Strata